(untitled) (Baghdad Science Journal, 2009)
The inhibitive effect of imidazol on the dissolution of Zn in (1M) HCl has been studied. The inhibion effect of imidazol ,protection efficiency and the corrosion rate of Zn in (1M) HCl were investigated at various concentrations (1x 10-3 – 5x10-3) M and tempearture range (285-328) K. The corrosion inhibitive of Zn by imidazol was studied using weight loss measurement and analytical titration of the amounts of dissolved zinc in acidic solution in presence and absent of imidazol. It was observed that imidazol led to protection efficiency reached to (88.93)% when (10)mM imidazol concentration was used. A linear relationship came true between (C/?) and (C); where (?) is the coverage of Zn surface by imidazol which could be obtained from the rate of corrosion in the presence and absent of inhibitor in the acid solution and (C) is the concentration of imidazol. This linear relationship indicate that the inhibition action occure via Langmiur adsorption mechanism. Eventually, the corrosion rates, activated energy ,Arrhenius constant, changes in free energy, enthalpy and entropy accompanying with imidazol adsorption on Zn surface were calculated.